Improving Science Learning Outcomes on Light and Optical Instruments Through Visual Methods in Junior High Schools - Retnani, Dewi Ria; Royani, Rina; Beccles, Christopher; Afras, Abderrachid (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: to improve science learning outcomes about light and optical devices through visual methods (learning by observing and describing) in class VIII junior high school students. Methodology: This type of research is classroom action research which is carried out in two cycles, namely cycle I and cycle II, each cycle contains planning, implementation, observation and reflection. The data collection method includes tests in the form of questions. Data analysis was carried out by calculating the achievement of learning outcomes for each cycle with an increase in classical completeness criteria, namely 85%. Main Findings: The research results show an increase in student learning outcomes through visual methods (learning by observing and describing) on the topic of light and optical devices. This research was successful with the average score increasing from 57.85% to 65.18% in the pre-cycle, increasing 21.42% in the first cycle, and reaching a class average of 81.42% with 96.42% completeness in the first cycle. cycle II, exceeding the target of 85% for classical completeness. Novelty/Originality of this study: The results of this research can contribute to scientific studies, especially on visual methods in learning in junior high schools. This research can be a guide for teachers to create interesting, effective and innovative learning, as well as increase students' enthusiasm for learning in science lessons through visual methods (learning by observing and imagining).